APPLYING BANKING DIGITIZATION MECHANISMS TO REDUCE BANK CREDIT RISKS: AN ANALYTICAL STUDY OF A SAMPLE OF IRAQI COMMERCIAL BANKS FOR THE PERIOD FROM (2010-2021) - A.P.Dr. Ahmed Sabeeh Attiya; Researcher: Inam Abdel Zahra Rahmah; Inam Adbalzahra Rahmah (Scholars Digest Publishing, 2024)
The current research dealt with two important variables: banking digitization as an independent variable, which is of great importance for processing, storing, and transferring data, as it works to improve customer relationships, generate more competitiveness, save costs, increase accuracy, and reduce banking risks, and credit risk as a dependent variable, which is the basic pillar in banking. Banks, which affect their work, and non-performing loans are one of their causes. Therefore, the research aimed to know the relationship between banking digitization and credit risks by analyzing the indicators of banking digitization and their relationship to avoiding credit risks. The research problem focused on the main question, which is: What is the role that it contributes to? Banking digitization in reducing bank credit risks? The research assumed the existence of correlation, influence, and causal relationships between banking digitization and credit risks in the research sample. The researchers followed the descriptive analytical approach. The research community included a sample of Iraqi commercial banks, namely (the National Bank of Iraq, the National Bank of Iraq, Commercial Gulf, and Bank of Baghdad), and for a period lasting (12) years extending from (2010 - 2021), as reliance was placed on data from the annual report of each bank and data provided by the Central Bank of Iraq, which were used in the practical aspect, and hypotheses were tested. The research was carried out through a set of financial analyzes and using the Excel program to extract growth rates. The research produced a set of results, the most prominent of which is the existence of a link and impact between banking digitization and credit risk in the research sample, as well as the existence of a causal relationship between these variables.
Keywords: banking digitization, credit risk.